Trauma and Lived Religion Transcending the Ordinary - Ganzevoort, R. Ruard; Sremac, Srdjan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book focuses on the power of the 'ordinary', 'everydayness' and 'embodiment' as keys to exploring the intersection of trauma and the everyday reality of religion. It critically investigates traumatic experiences from a perspective of lived religion, and therefore, examines how trauma is articulated and lived in the foreground of people's concrete, material actualities. Trauma and Lived Religion seeks to demonstrate the vital relevance between the concept of lived religion and the study of trauma, and the reciprocal relationship between the two. A central question in this volume therefore focuses on the key dimensions of body, language, memory, testimony, and ritual. It will be of interest to academics in the fields of sociology, psychology, and religious studies with a focus on lived religion and trauma studies, across various religions and cultural contexts. .
Trauma and Lived Religion: Embodiment and Emplotment, Srdjan Sremac and R. Ruard Ganzevoort -- Part I. Body -- Torture and Lived Religion: Practices of Resistance, Kathryn House -- Disgust, Shame, and Trauma: The Visceral and Visual Impact of Touch, Stephanie N. Arel -- Part II. Meaning -- Significance of the "Visceral" in Lived Religion Studies of Trauma, Michelle A. Walsh -- Traumics: The Church and Trauma in Comic Book Format, Maike Schult -- Part III. Relationship -- The Function of Religion in the Context of Re-Experiencing Trauma: Analyzing a Case Study with the Concepts of Transformational and Transitional Object, Hanneke Schaap-Jonker -- Trauma in Relationship - Healing by Religion: Restoring Dignity and Meaning after Traumatic Experiences, Mariéle Wulf -- Part IV. Testimony -- Lived Religion and the Traumatic Impact of Sexual Abuse: The Sodalicio Case in Peru, Rocio Figueroa Alvear and David Tombs -- Feeding the Hungry Spirits: A Socially Engaged Buddhist Response to the Distortion of Trauma, Jürgen Jian Lembke and Julianne Funk. - Part V. Ritual -- Remembering for Healing: Liturgical Communities of Reconciliation Provide Space for Trauma, Armand Léon van Ommen -- Victimization via Ritualization: Christian Communion and Sexual Abuse, Hilary Jerome Scarsella.
Keywords: Religion and sociology; Psychology and religion; Criminal behavior; Sociology of Religion; Psychology of Religion and Spirituality; Criminal Behavior